Naluri Kekuasaan dalam Sigmund Freud - Juraman, Stefanus Rodrick (Jurnal Studi Komunikasi, 2017)
Sigmund Freud is a psychologist who develops dynamic psychology. In this case, Freud develops the personality that shapes man. In a book written by Calvin S. Hall entitled Naluri Kekuasaan. The book describes the Freud from history about himself to the composition of personality. Sigmund Freud put forward the Theory of Psychoanalysis as the formation of human personality or the development of the psychiatric.